Dichotomous role of Shp2 for naïve and primed pluripotency maintenance in embryonic stem cells - Seong-Min Kim; Eun-Ji Kwon; Yun-Jeong Kim; Young-Hyun Go; Ji-Young Oh; Seokwoo Park; Jeong Tae Do; Keun-Tae Kim; Hyuk-Jin Cha (Stem Cell Research & Therapy, 2022)
Abstract Background The requirement of the Mek1 inhibitor (iMek1) during naïve pluripotency maintenance results from the activation of the Mek1-Erk1/2 (Mek/Erk) signaling pathway upon leukemia inhibitory factor (LIF) stimulation. Methods Through a meta-analysis of previous genome-wide screening for negative regulators of naïve pluripotency, Ptpn11 (encoding the Shp2 protein, which serves both as a tyrosine phosphatase and putative adapter), was predicted as one of the key factors for the negative modulation of naïve pluripotency through LIF-dependent Jak/Stat3 signaling. Using an isogenic pair of naïve and primed mouse embryonic stem cells (mESCs), we demonstrated the differential role of Shp2 in naïve and primed pluripotency. Results Loss of Shp2 increased naïve pluripotency by promoting Jak/Stat3 signaling and disturbed in vivo differentiation potential. In sharp contrast, Shp2 depletion significantly impeded the self-renewal of ESCs under primed culture conditions, which was concurrent with a reduction in Mek/Erk signaling. Similarly, upon treatment with an allosteric Shp2 inhibitor (iShp2), the cells sustained Stat3 phosphorylation and decoupled Mek/Erk signaling, thus iShp2 can replace the use of iMek1 for maintenance of naïve ESCs. Conclusions Taken together, our findings highlight the differential roles of Shp2 in naïve and primed pluripotency and propose the usage of iShp2 instead of iMek1 for the efficient maintenance and establishment of naïve pluripotency.